Multimodal Interactive Pedagogy for Early Caries Detection: A Short-Term Assessment of Health Literacy in Transitional Dentition - Rahmi Khairani Aulia; Suci Rahmasari; Haria Fitri; Yona Ladyventini; Rahmatul Aini (HM Publisher, 2026)
Dental caries is a pervasive non-communicable disease, affecting approximately 80% of children in Indonesia. Children in the transitional dentition phase (aged 7–8 years) frequently lack awareness regarding oral health. Traditional educational models often fail to instill long-term behavioral changes. This study aims to evaluate the short-term impact of an interactive multimodal educational intervention grounded in the Health Belief Model on the early caries detection knowledge of 7-8-year-old schoolchildren in an urban middle-income setting. A quantitative pre-experimental, one-group pre-test and post-test design was utilized. A convenience sample of 57 grade 2 students from SD IT Cendikia Andalas participated. The intervention deployed tactile dental models, posters, and animated videos. The curriculum detailed anatomical function, caries etiology, early visual detection, and preventive strategies. Knowledge was measured using a validated 5-item questionnaire focusing on pathophysiology and visual cueing. Descriptive statistics included Medians and Interquartile Ranges (IQR). Hypothesis testing utilized the Wilcoxon Signed Rank Test. The cohort demonstrated a statistically significant short-term increase in knowledge. The pre-test Median score was 4.0 (IQR: 3.0–4.0), which increased post-intervention to a Median of 5.0 (IQR: 4.0–5.0) (p < 0.001). Both female (p < 0.001) and male (p < 0.001) subgroups showed significant improvements. Identification of white spot lesions improved from 35.1% to 87.7%. In conclusion, multimodal education is associated with a significant short-term increase in early caries detection knowledge among young schoolchildren. Integrating such interactive modules into longitudinal curricula alongside parental involvement is recommended for sustained public health impact.